Direct and indirect relationships of climate and land use change with food webs in lakes and streams - Barbosa, Gedimar Pereira [UNESP]; Siqueira, Tadeu [UNESP] (Wiley, 2023)
Aim: Climate and land use change can independently affect food web structure. However, their direct and indirect relationships with food webs are not well-understood. This is particularly relevant for freshwater ecosystems, which are strongly affected by global threats and differ substantially in attributes and functioning. Here, we investigated direct and indirect relationships between climate and land use changes and freshwater food web structure, while considering the differences between lakes and streams. Location: Multicontinental. Time period: Current. Major taxa studied: Freshwater taxa. Methods: We compiled 51 food webs, spanning 12 countries and six continents to investigate the direct and indirect relationships between land use intensity, changes in air temperature and precipitation and food web structure, using structural equation modelling (SEM). We further tested how lake and stream food webs differ in their responses to environmental change by applying a multigroup analysis to our SEM. Results: We found that connectance was positively related to both land use intensity and increases in air temperature and precipitation in stream food webs, whereas in lakes, it was only related to temperature. These findings suggest a dominance of generalists where conversion to agriculture and urbanization has been intensified, and temperature has increased. Food web vertical structure was negatively related to land use and increases in air temperature and precipitation, but climatic predictors were only linked to network structure through a negative relationship with the fraction of top consumers. Main conclusions: While land use intensity was directly related to food web structure, complex relationships between changes in climate and network topology were mediated by the fraction of top consumers. Also, as food webs in lakes and streams responded differently to land use and climate change, we suggest that their intrinsic characteristics must be explicitly considered to fully understand the effects of global changes on freshwater biodiversity.
Keywords: connectance; freshwater; networks; precipitation; structural equation modelling; temperature; trophic interactions